Ecology and Ecumenism in Europe: A Way Forward - Johnson, Donald Bruce (Journal for the study of religion, nature and culture, 1998)
Introduction As we stand on the threshold of a new millennium, it is only natural to ask what sort of world we will pass on to the dwellers of those coming centuries. It seems clear that our legacy will be both blessing and curse. To some at least we will hand over benefits in communication, mobility and technical possibilities. To many we will bequeath unprecedented problems, as the effects of global warming inexorably take their course, as gridlock and pollution choke the world’s cities, and as water and soils become increasingly vulnerable. There are some good signs, but many in the secular environmental sphere feel powerless and frustrated at how little we have all done to reduce those heavy burdens our descendants will inherit.